Differential behavioural and endocrine responses of common voles (Microtus arvalis) to nest predators and resource competitors - Liesenjohann, Monique; Liesenjohann, Thilo; Palme, Rupert; Eccard, Jana (Prof. Dr.) (2017)
Background: Adaptive behavioural strategies promoting co-occurrence of competing species are known to result from a sympatric evolutionary past. Strategies should be different for indirect resource competition (exploitation, e.g., foraging and avoidance behaviour) than for direct interspecific interference (e.g., aggression, vigilance, and nest guarding). We studied the effects of resource competition and nest predation in sympatric small mammal species using semi-fossorial voles and shrews, which prey on vole offspring during their sensitive nestling phase. Experiments were conducted in caged outdoor enclosures. Focus common vole mothers (Microtus arvalis) were either caged with a greater white-toothed shrew (Crocidura russula) as a potential nest predator, with an herbivorous field vole (Microtus agrestis) as a heterospecific resource competitor, or with a conspecific resource competitor. Results: We studied behavioural adaptations of vole mothers during pregnancy, parturition, and early lactation, specifically modifications of the burrow architecture and activity at burrow entrances. Further, we measured pre- and postpartum faecal corticosterone metabolites (FCMs) of mothers to test for elevated stress hormone levels. Only in the presence of the nest predator were prepartum FCMs elevated, but we found no loss of vole nestlings and no differences in nestling body weight in the presence of the nest predator or the heterospecific resource competitor. Although the presence of both the shrew and the field vole induced prepartum modifications to the burrow architecture, only nest predators caused an increase in vigilance time at burrow entrances during the sensitive nestling phase. Conclusion: Voles displayed an adequate behavioural response for both resource competitors and nest predators. They modified burrow architecture to improve nest guarding and increased their vigilance at burrow entrances to enhance offspring survival chances. Our study revealed differential behavioural adaptations to resource competitors ...